КРАТКОЕ СОПОСТАВЛЕНИЕ СЕМАНТИЧЕСКОЙ ДЕРИВАЦИИ В АНГЛИЙСКОМ И КАРАКАЛПАКСКОМ ЯЗЫКАХ - Сагатова, З.Б. (SCIENCE and SOCIETY, 2022)
The article dwells on some results of a comparative-typological study of the mechanism of semantic derivation of nouns in English and Karakalpak. The similarities and differences between the semantic and derivational processes and their causes in the studied languages are described and analyzed.
Keywords: semantic derivation; the English language; the Karakalpak language; polysemy; homonymy; word formation